Electrocoagulation and advanced electrocoagulation processes: A general review about the fundamentals, emerging applications and its association with other technologies - Garcia-Segura, Sergi; Eiband, Maria Maesia S.G.; de Melo, Jailson Vieira; Martínez-Huitle, Carlos Alberto [UNESP] (Elsevier, 2017)
The electrocoagulation (EC) process is an electrochemical means of introducing coagulants and removing suspended solids, colloidal material, and metals, as well as other dissolved solids from water and wastewaters. EC process has been successfully employed in removing pollutants, pesticides, and radionuclides. This process also removes harmful microorganisms. More often during EC operation, direct current is applied and electrode plates are sacrificed (dissolved into solution). The electrodissolution causes an increased metal concentration in the solution that finally precipitates as oxides and hydroxides. Due to the process design and low cost material, the EC process is widely accepted over other physicochemical processes. In this frame, this paper presents a general review of efficient EC technologies developed to remove organic and inorganic matter from wastewaters for environmental protection. Fundamentals and main applications of EC as well as progress of emerging EC treatments are reported. The influence of iron or aluminum anode on depollution of synthetic or real effluents is explained. The advantages of EC mechanisms with Al and Fe electrodes are extensively discussed. There are presented the advanced EC processes with in situ generation of hydroxyl radical. The importance of the operating parameters for efficient application of the EC process as well as the combination of this electrochemical technology with electroanalysis techniques and other technologies are commented.
Keywords: Electrochemical reactor; Electrocoagulation; Electroflotation; Wastewater treatment